Sleeping giants : a novel - Denfeld, Rene (Harper, 2024)
"Twenty years ago, a nine-year-old boy was swept away by powerful waves on a remote Oregon beach, his body lost to the sea. Only a stone memorial remains to mark his tragic death. For most of her life, Amanda Dufresne had no idea she had an older brother named Dennis Owens, or that he had died. Adopted as a baby, she learned about him while looking into her late birth mother, and is curious to know more about this lost sibling. A solitary young woman, Amanda has always felt distanced from the world around her. Her brain works differently from others, leaving her feeling set apart. Her one true companion is the orphaned polar bear she cares for working at the zoo. By getting to know her birth family, she hopes to understand more about herself. Retired police officer Larry Palmer is a widower with nothing but time and in need of a purpose. He offers to help Amanda find answers. The search leads to shocking and heartbreaking discoveries. Dennis Owen had been a forgotten foster child abandoned to a home for disturbed boys off the coast. As Amanda and Larry dig deeper into the past, the two stumble upon decades of cruelty and hidden crimes--including a barbaric treatment still used today"--